2008
DOI: 10.1080/07399330802523568
|View full text |Cite
|
Sign up to set email alerts
|

Enculturation as a Condition Impacting Korean American Physicians' Responses to Korean Immigrant Women Suffering Intimate Partner Violence

Abstract: We explored how Korean American (KA) physicians in the Los Angeles area respond in their medical practice to Korean immigrant women with a history of intimate partner violence (IPV). Twenty physicians were recruited and interviewed in-depth. Grounded theory analyses revealed that KA physicians' responses to IPV ranged from denying signs of IPV and trivializing IPV to acknowledging IPV. Physician response was related to the degree to which he or she was enculturated in mainstream medical practice norms in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…With regard to opinions towards IPV, although they are usually positive, negative opinions have also been documented among healthcare professionals. Thinking that it is a private and personal problem related to women, which cannot be addressed by the public health system [ 16 , 36 , 37 ], or related to a specific group of women [ 38 ], the result of a personal decision [ 39 ], or that there may be reasons justifying it [ 40 ] have all been related to healthcare professionals’ decisions not to assess IPV, or to have a limited response [ 17 ]. These opinions are based on traditional beliefs or false myths about IPV, whose goal it is to justify, minimise, or deny this type of violence from men to women within a relationship [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to opinions towards IPV, although they are usually positive, negative opinions have also been documented among healthcare professionals. Thinking that it is a private and personal problem related to women, which cannot be addressed by the public health system [ 16 , 36 , 37 ], or related to a specific group of women [ 38 ], the result of a personal decision [ 39 ], or that there may be reasons justifying it [ 40 ] have all been related to healthcare professionals’ decisions not to assess IPV, or to have a limited response [ 17 ]. These opinions are based on traditional beliefs or false myths about IPV, whose goal it is to justify, minimise, or deny this type of violence from men to women within a relationship [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found the prevalence of violence against men to be equivalent to that against women [18,19]. Similarly, in South Korea, previous research has highlighted the scope and risk factors of violence against women; however, few studies have investigated the prevalence of violence against men or the possible risk factors associated with male perpetration and victimization [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Additional research explored the perspectives of health professionals who encounter domestic violence in their work with Korean immigrant women (Chung, Oswald, & Hardesty, 2009; Shim & Hwang, 2005) and South Asian immigrant women (Kallivayalil, 2007). For example, interviews with Korean American physicians indicated the importance of considering the physician’s level of adherence to U.S. cultural medical practice norms in their response to IPV.…”
Section: Resultsmentioning
confidence: 99%
“…For example, interviews with Korean American physicians indicated the importance of considering the physician's level of adherence to U.S. cultural medical practice norms in their response to IPV. More specifically, Chung et al (2009) found that Korean American physicians with lower adherence to U.S. norms were less likely to take more subtle indices of IPV seriously.…”
Section: General Attributions/perceptions Of Mental Healthmentioning
confidence: 98%